ANALISIS KETERJANGKAUAN DAYA BELI PENGGUNA JASA TRANSPORTASI UDARA UNTUK RUTE DARI KABUPATEN KEPULAUAN SULA KE KOTA TERNATE - Nurul Ilma Sukardi; Arbain Tata; Raudha Hakim (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2022)
One of the available modes of transportation for the Sula Islands Regency-Ternate City Route is air transportation. This mode has been operating for the past three years, becoming an alternative mode for people who do not want to use water transportation modes. One of the important factors in managing transportation is the cost of travel offered. In the air transportation mode itself, the current travel costs cannot be reached by all levels of society, especially those with low incomes. Therefore, a study was conducted on the ability to pay (ATP) and willingness to pay (WTP) in accordance with the level of people's income. This research is a quantitative research where the results obtained from the distribution of questionnaires will be analyzed and converted into numbers. The appropriate travel costs from the research results are the average ATP based on the allocation of transportation costs, which is Rp. 350,000, - and the average WTP for all job categories, which is Rp. 347,167, - .